Inverse estimation of breaking wave loads on monopile wind turbines. (1st September 2018) - Maes, K.; Weijtjens, W.; de Ridder, E.-J.; Lombaert, G.
Abstract: Breaking waves occur in shallow water and cause large forces on offshore wind turbines, which can determine the design of the support structure. Due to the strong nonlinearity and statistical variability of breaking waves, the corresponding loads used in the design are generally characterized by large uncertainty. This paper presents a validation of an inverse method to estimate breaking wave loads on offshore monopile wind turbines based on wave basin tests. The accelerations measured on a scale model of a monopile wind turbine are passed to a force identification algorithm together with a dynamic model of the structure in order to identify the wave loads. In addition, the member forces in the support structure are estimated. Both the wave loads and member forces are estimated with a reasonable accuracy. The proposed methodology creates opportunities for operational monitoring of offshore wind turbines, hereby providing essential information to improve design guidelines for future wind turbines and allowing for a continuous fatigue assessment of the wind turbine during the operation. Highlights: An inverse method is used to identify breaking wave loads on offshore monopile wind turbines. A validation is performed using data obtained from wave basin tests. The wave loads and member forces in the monopile are identified with good accuracy. The methodology creates opportunities for operational monitoring of offshore wind turbines.